2020
DOI: 10.31234/osf.io/ef9ch
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The power of everyday peer relatedness in predicting subjective well-being and adjustment after secondary school transition

Abstract: Secondary school transition represents a challenging life event. This study examines108 children in Germany during the first 12 weeks of adapting to the new school. Daily satisfaction and frustration of the basic need for relatedness were examined aspredictors of subjective well-/ill-being and adjustment/psychopathology. Subjectivewell-/ill-being were assessed at Weeks 3-4 and Week 11 of the school year. In between, there was a 4-week period of daily assessments of perceived relatednesssatisfaction and frustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In our studies, we used positively worded items to measure self-esteem and we found significant associations with positive peer experiences. Future studies should examine whether negative peer experiences might be linked to a negative side of self-esteem that was not assessed in the present studies, as related research has found such differential effects between social inclusion and exclusion with positive and negative affect, for instance (Bartholomew et al, 2011;Schmidt et al, 2019Schmidt et al, , 2020aSchmidt et al, , 2020b. Identifying different antecedents of a positive and a negative side of self-evaluations would demonstrate the necessity to distinguish two factors, as suggested by Huang and Dong (2012).…”
Section: Is Good Stronger Than Bad?mentioning
confidence: 83%
See 2 more Smart Citations
“…In our studies, we used positively worded items to measure self-esteem and we found significant associations with positive peer experiences. Future studies should examine whether negative peer experiences might be linked to a negative side of self-esteem that was not assessed in the present studies, as related research has found such differential effects between social inclusion and exclusion with positive and negative affect, for instance (Bartholomew et al, 2011;Schmidt et al, 2019Schmidt et al, , 2020aSchmidt et al, , 2020b. Identifying different antecedents of a positive and a negative side of self-evaluations would demonstrate the necessity to distinguish two factors, as suggested by Huang and Dong (2012).…”
Section: Is Good Stronger Than Bad?mentioning
confidence: 83%
“…Daily social inclusion and exclusion were operationalized as the mean response across the four items, respectively. The items were used in previous studies (see Schmidt et al, 2019Schmidt et al, , 2020aSchmidt et al, , 2020b. Evidence for convergent and divergent validity of these scales can be found in these papers, demonstrating the psychometric separation of social inclusion and exclusion 3 and showing differential effects on positive and negative outcomes.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation